La literatura de mujeres como archivo hospitalario: una propuesta - Szurmuk, Mónica (Universidad Nacional del Litoral, 2020)
In this article, we analyze the specific contributions of literature in the reconstruction of the presence of women in history. Drawing from Jacques Derrida, we propose the concept of hospitable archive to account for the selection of a new literary canon. Furthermore through attention to what we call hospitable archive, we put forth novel ways of reading that are attentive to what is suggested or repressed in these texts, and to what could not signify in the context of production and publication, but acquires new life in a contemporary reading. From this perspective we analyze works by Sor Juana Inés de la Cruz (and the actualization of her poetry in Jesusa Rodríguez´s performance), Sabina Berman, Lina Beck-Bernard and Tununa Mercado.